THE INFLUENCE OF DIGITAL MARKETING, PRODUCT CREATIVITY AND SERVICE QUALITY ON MARKETING PERFORMANCE AT PT. CIPTA VARIOUS TASTES (C BEZT EAST JAVA) - Molektuzzahro, Arila; Santoso, Budi; Fatimah, Feti (Univesitas Muhammadiyah Tangerang, 2024)
As a developing country, Indonesia is a potential market. New businesses in the food and beverage industry emerged as a result of the Indonesian people's tendency to like fast food. The aim of this research is to identify the factors that influence PT's marketing performance. Cipta Aneka Selera, including digital marketing, product creativity and service quality. It is hoped that this research will be useful as a source of evaluation and information regarding the influence of digital marketing, product creativity and service quality on marketing performance. Therefore, it is hoped that this research will be useful in determining PT's marketing strategy. Create a variety of tastes more effectively. This research uses associative quantitative methods. In this research, the manager of PT. Cipta Aneka Selera throughout East Java was involved. A total of 87 people who answered were taken as a saturated sample. The research results show that digital marketing, product creativity and service quality have a positive and significant effect on PT's marketing performance. Create Various Tastes.